Efficient methods for preparing silicon compounds - Roesky, H. W. (London, UK : Academic Press is an imprint of Elsevier, 2016)
Efficient Methods for Preparing Silicon Compounds is a unique and valuable handbook for chemists and students involved in advanced studies of preparative chemistry in academia and industry. Organized by the various coordination numbers (from two to six) of the central silicon atom of the reported compounds, this book provides researchers with a handy and immediate reference for any compound or properties needed in the area. Edited by a renowned expert in the field, each chapter explores a different type of compound, thoroughly illustrated with useful schemes and supplemented by additional references. Knowledgeable contributors report on a broad range of compounds on which they have published and which are already used on a broad scale or have the potential to be used in the very near future to develop a new field of research or application in silicon chemistry.
Includes index.
Online resource; title from PDF title page (ScienceDirect, viewed June 29, 2016).
Includes bibliographical references and index.
Keywords: Silicon compounds; Silicon compounds; SCIENCE / Chemistry / Inorganic; Electronic books